2021
DOI: 10.3390/biology10090861
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Oxygen Flight Sensitivity in Ageing Drosophila melanogaster Flies: Links to Rapamycin-Induced Cell Size Changes

Abstract: Ectotherms can become physiologically challenged when performing oxygen-demanding activities (e.g., flight) across differing environmental conditions, specifically temperature and oxygen levels. Achieving a balance between oxygen supply and demand can also depend on the cellular composition of organs, which either evolves or changes plastically in nature; however, this hypothesis has rarely been examined, especially in tracheated flying insects. The relatively large cell membrane area of small cells should inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 143 publications
(194 reference statements)
0
22
0
Order By: Relevance
“…In addition, RAPTOR was upregulated in a study of cold resistance in Drosophila [ 51 ]. A recent study on thermal and oxygen flight sensitivity in Drosophila showed that downregulation of TOR activity produces smaller flies with smaller wing epidermal cells, and flies with small cells can maintain superior performance in metabolically demanding activities, such as flying under hypoxic conditions [ 52 ]. Whether A. cerana has adopted the same strategy as other insects to combat different climate types requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RAPTOR was upregulated in a study of cold resistance in Drosophila [ 51 ]. A recent study on thermal and oxygen flight sensitivity in Drosophila showed that downregulation of TOR activity produces smaller flies with smaller wing epidermal cells, and flies with small cells can maintain superior performance in metabolically demanding activities, such as flying under hypoxic conditions [ 52 ]. Whether A. cerana has adopted the same strategy as other insects to combat different climate types requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Transfers prevented generational overlap. Following our previous approach [29], we produced two consecutive generations under conditions of controlled larval density. Upon each transfer, we placed 10 females and 5 males from each isoline in a vial for 48 h for oviposition.…”
Section: Methodsmentioning
confidence: 99%
“…We used 14 genetic isolines from a wild population of D. melanogaster established in 2017 (49°58'00.8″ N, 20°29'54.1″ E) and maintained at the Institute of Environmental Sciences (Jagiellonian University, Kraków, Poland) [29]. Flies were maintained in vials (polyurethane vials with foam plugs) with cornmeal yeast medium (Bloomington Drosophila Stock Center, Bloomington, USA) in 40-ml vials (with 10 ml of food) in the stock population and in 68-ml vials (with 20 ml of food) for the study population.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations